Reorganization of action observation and sensory‐motor networks after action observation therapy in children with congenital hemiplegia: A pilot study. Issue 9 (28th October 2020) - Sgandurra, Giuseppina; Biagi, Laura; Fogassi, Leonardo; Ferrari, Adriano; Sicola, Elisa; Guzzetta, Andrea; Tosetti, Michela; Cioni, Giovanni
Abstract: New rehabilitation programs based on action observation therapy (AOT) are effective in improving motor function in children with congenital hemiplegia. In this pilot study we tested the potential effects of AOT on the reorganization of the motor system by functional magnetic resonance imaging (fMRI). As part of a randomized trial, eight subjects (age range: 6.2–14.5 years) with congenital hemiplegia were randomly assigned to an experimental (EG) or control (CG) group. All children underwent a clinical and neurophysiological assessment with Assisting Hand Assessment (AHA), MRI, and fMRI at baseline (T0), 1(T1), and 8(T2) weeks after the end of 3‐week treatment. For the EG, AOT consisted in the observation of uni/bimanual goal‐directed actions followed by their execution. CG watched same‐duration computer games and then performed the same actions in the same order used in the EG. fMRI study was carried out using two different paradigms, for exploring sensory‐motor network (SMN) localization and action observation network (AON). The pattern of brain activation was generally similar between T0 and T1 for both groups, while it was more widespread at T2, compared to T0 and T1, in the EG. This enlargement was coupled with functional improvement at AHA. Single‐subject analysis shows a reduction of lateralization indexes both for the AON and the SMN. This pilot study, despite the small sample, showed the fMRI feasibility for providing relevant biomarkers of brain plasticity for monitoring the AOT response in children with congenital hemiplegia. The study was registered at http://www.clinicaltrials.gov (identifier NCT01016496).